SISTEM PENUNJANG KEPUTUSAN INTELIJEN CHAOTIC UNTUK STRATEGI PENGEMBANGAN AGROINDUSTRI UBIKAYU - Pudji Astuti (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
This study is aimed to design a generic decision support system on early warning system for cassava agroindustry. The intelligent system was established as controlling tools through formulating policies for managing crisis as impact of chaotic occurences. This integrated system was formulated using computer program consist of 5 models which are: variable identify source of turbulence designed with Fuzzy Pairwise Comparation, chaotic investigation model designed with chaos theory approach, Price and material supply forecasting model designed with Artificial Neural Network. Crisis warning model was set up with threshold analysis, and supplemented with control management procedure. When Price or material supply was evaluated at crisis level, then option of recovery will be presented. The inteligent System was implemented in user friendly decisión support system named CHAOTICA ( Chaos Theory for Cassava Agroindustry).